A nexus approach to groundwater and cooperation - Ringler, Claudia (CGIAR, 2024)
A session held at Stockholm World Water Week 2024, titled ‘Managing water from the ground up: Challenges and opportunities,’ presented groundwater policies and active management cases from Brazil, Ethiopia, Pakistan, and the USA, and identified opportunities for collaborative action to prevent conflict.